Different roles of distinct serotonergic pathways in anxiety-like behavior, antidepressant-like, and anti-impulsive effects. (1st May 2020) - Ohmura, Yu; Tsutsui-Kimura, Iku; Sasamori, Hitomi; Nebuka, Mao; Nishitani, Naoya; Tanaka, Kenji F.; Yamanaka, Akihiro; Yoshioka, Mitsuhiro
Abstract: Serotonergic agents have been widely used for treatment of psychiatric disorders, but the therapeutic effects are insufficient and these drugs often induce severe side effects. We need to specify the distinct serotonergic pathways underlying each mental function to overcome these problems. Preclinical studies have demonstrated that the central serotonergic system is involved in several emotional/cognitive functions including anxiety, depression, and impulse control, but it remains unclear whether each function is regulated by a different serotonergic system. We used optogenetic strategy to increase central serotonergic activity in mice and evaluated the behavioral consequences. Pharmacological and genetic tools were used to determine the subtype of 5-HT receptors responsible for the observed effects. We demonstrated that the serotonergic activation in the median raphe nucleus enhanced anxiety-like behavior, the serotonergic activation in the dorsal raphe nucleus exerted antidepressant-like effects, and the serotonergic activation in the median or dorsal raphe nucleus suppressed impulsive action. We also found that different serotonergic terminals, ventral hippocampus, ventral tegmental area/substantia nigra, and subthalamic/parasubthalamic nucleus, are involved in regulating anxiety-like behavior, antidepressant-like, and anti-impulsive effects, respectively. Furthermore, we found, using triple-transgenic mice, that the stimulation of the 5-HT2C receptor is required to evoke anxiety-like behavior, but not to exert anti-impulsive effects. These results suggest the need for pathway-specific treatments and provide important insights that will help the development of more effective and safer therapeutics. This article is part of the special issue entitled 'Serotonin Research: Crossing Scales and Boundaries'. Highlights: Median and dorsal raphe nuclei differentially regulate each emotional function. Serotonergic terminals in the ventral hippocampus regulate anxiety-like behavior. The ventral tegmental area/substantia nigra regulates antidepressant-like effects. The subthalamic/parasubthalamic nucleus regulates anti-impulsive effects. 5-HT2C receptor is required to evoke anxiety-like behavior.